Al-Suyūṭī, a polymath of the Mamlūk period
1 online resource (240 pages)
Keywords: This volume is a collection of several papers devoted to Jalāl al-Dīn al-Suyūṭī (d. 911/1505), presented on the First Conference of the School of Mamlūk Studies (held at Ca’ Foscari University,Venice, from June 23 to June 25, 2014). It aims to contribute to a reassessment of the scholarly profile of the controversial but fascinating polymath and intellectual, and, more generally, to a deeper understanding of the cultural, political and academic life of the last period of the Mamlūk empire. Jalāl al-Dīn al-Suyūṭī's bibliography ranges from law to theology, and from linguistics to history. It includes medicine and geography. This polymath felt that his mission was to preserve the rich cultural heritage of the past, and knowledge in general, from widespread ignorance and decline. Considered for a long time to be an author devoid of any originality and a “simple” compiler, he was in fact an excellent teacher and a rigorous scholar who had a meticulous and accurate working method. With contributions by: Christopher D. Bahl; Mustafa Banister; Joel Blecher; S. R. Burge; Daniela Rodica Firanescu; Éric Geoffroy; Antonella Ghersetti; Francesco Grande; Jaakko Hämeen-Anttila; Takao Ito; Judith Kindinger; Christian Mauder; Aaron Spevack.